Growth and visibility of Latin American and Caribbean law journals (2008-2023): A focus on their language, collaboration, and open access trends - Lendvai, Gergely (Iberoamerican Journal of Science Measurement and Communication, 2025)
Objective. The objective of this study was to examine the factors that have contributed to the growth and visibility of Latin American and Caribbean (LAC) law journals between 2008 and 2023. In particular, the impact of open access (OA) policies, national policies, and authorship trends will be investigated. Design/Methodology/Approach. The study employed data from the Scopus database to analyze metrics such as SCImago Journal Rank, citation rates, and authorship patterns. It compared the growth trends of law journals from Brazil, Chile, and other LAC countries, as well as examining the role of OA platforms such as SciELO and regional collaboration. Results/Discussion. The study revealed a significant increase in the number of indexed LAC law journals, particularly in Brazil, which grew from zero journals in 2008 to 34 by 2023. Chile also experienced an expansion, with an increase from four journals to thirteen. The findings highlighted the importance of OA policies, which have contributed to increased visibility and higher citation rates, especially for publications in Spanish and Portuguese. Conclusions. The global impact of LAC law journals had increased as a result of a combination of OA policies, strong domestic authorship, and regional collaboration. The use of multiple languages, primarily Spanish and Portuguese, had facilitated regional participation, while English-language publications had also expanded to enhance global visibility. Originality/Value. The paper adds novelty to the developing scientometric area on the emergence of LAC law journals, as it offers insights into the regional factors that contribute to their visibility and international impact.